2020
DOI: 10.1002/cb.1860
|View full text |Cite
|
Sign up to set email alerts
|

Leave or stay? The role of self‐construal on luxury brand attitudes and purchase intentions in response to brand rejection

Abstract: Marketing managers of luxury brands often use exclusionary marketing tactics that can lead consumers to feel rejected by those brands. In our research, we examine whether consumers with independent self‐construals are more likely than those with interdependent self‐construals to downgrade their evaluations of a luxury brand when feeling rejected by it. Results of three studies support this hypothesis. Using a manipulation of brand rejection with hypothetical future scenarios, study 1 provides evidence that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Aghakhani and Main (2019); Baek et al (2018); Baek et al (2019); Bozkurt and Gligor (2019); Chen et al (2017); Dommer et al (2013); Duclos et al (2013); El Hazzouri et al (2017); Gao and Mattila (2016); Guèvremont and Grohmann (2016); Han et al (2015); Hu et al (2018); Jiang et al (2018); Jiang et al (2020); Jiao and Wang (2018); Kandaurova and Lee (2019); Khalifa and Shukla (2017); Kim, Park, et al (2020); Lee et al (2017); Lee and Shrum (2012); Liang et al (2018); Liang and Chang (2016); Liu et al (2021); Loveland et al (2010); Lu and Sinha (2017); Mead et al (2011); Mourey et al (2017); Newman et al (2019); Sinha and Lu (2019); Sinha and Wang (2013); Su et al (2017); Su et al (2019); Tezer and Bodur (2020); Thomas and Saenger (2020); Tunçel and Kavak (n.d.); Vinuales and Thomas (2021); Wan et al (2014); Wang et al (2012); Wang and Ding (2017); Wang and Lalwani (2019); Ward and Dahl (2014); Wu and Dodoo (2020); Xie, Chen and Guo (2020); Xu and Jin (2020); Yang et al (2020); Yi et al (2017)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aghakhani and Main (2019); Baek et al (2018); Baek et al (2019); Bozkurt and Gligor (2019); Chen et al (2017); Dommer et al (2013); Duclos et al (2013); El Hazzouri et al (2017); Gao and Mattila (2016); Guèvremont and Grohmann (2016); Han et al (2015); Hu et al (2018); Jiang et al (2018); Jiang et al (2020); Jiao and Wang (2018); Kandaurova and Lee (2019); Khalifa and Shukla (2017); Kim, Park, et al (2020); Lee et al (2017); Lee and Shrum (2012); Liang et al (2018); Liang and Chang (2016); Liu et al (2021); Loveland et al (2010); Lu and Sinha (2017); Mead et al (2011); Mourey et al (2017); Newman et al (2019); Sinha and Lu (2019); Sinha and Wang (2013); Su et al (2017); Su et al (2019); Tezer and Bodur (2020); Thomas and Saenger (2020); Tunçel and Kavak (n.d.); Vinuales and Thomas (2021); Wan et al (2014); Wang et al (2012); Wang and Ding (2017); Wang and Lalwani (2019); Ward and Dahl (2014); Wu and Dodoo (2020); Xie, Chen and Guo (2020); Xu and Jin (2020); Yang et al (2020); Yi et al (2017)…”
Section: Methodsmentioning
confidence: 99%
“…Moving forward, it was found that the majority of the reviewed studies were based on responses from North America and China. A few studies have captured responses from multiple countries with the help of online consumer panels like Amazon Mturk (Han et al, 2015;Wang & Lalwani, 2019;Ward & Dahl, 2014;Yi et al, 2017) or through cross cultural studies to compare consumption responses across contrasting cultures (Lee et al, 2017;Liu et al, 2021). Other populations, specifically of the South Asian subcontinent, have rarely been touched upon, and need urgent attention.…”
Section: Contextual Factors In Social Exclusion Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Brand preference is positively influenced by customer attitudes (Hwang & Ok, 2013). Consumer attitudes toward luxury brands have a significant impact on customer intention, which in turn has a positive impact on luxury brand actual usage (Liu et al, 2021). Consumer attitudes are important in predicting brand attachment, willingness to pay more, and brand value (Hwang & Hyun, 2017).…”
Section: Customer Attitudementioning
confidence: 99%
“…Luxury goods have been important objects of study in the most diverse areas, with the reasons driving their consumption being among the main topics researched (e.g., Kastanakis & Balabanis, 2012; Tseng et al, 2021). The investigation of consumers' choices (Kauppinen‐Räisänen et al, 2018), feelings (Amatulli et al, 2018), and reactions (Liu et al, 2021) gained in prominence, as the search for superior quality (Wiedmann et al, 2009) and social status (Balabanis & Stathopoulou, 2021) support – at least partially – the high value attributed to luxury brands (Stokburger‐Sauer & Teichmann, 2013). Whereas studying the psychological (Prestini & Sebastiani, 2021), economic (Zhan & He, 2012), and sociological (Wong & Ahuvia, 1998) aspects that influence the demand for luxury is critical, understanding those factors that may harm it is equally important.…”
Section: Introductionmentioning
confidence: 99%